(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2019)
The paper deals with the possibility of using the so-called "island operation" for feeding the electrolyser for the production of hydrogen. A series of 2000W photovoltaic panels is used for power generation in island operation. The electricity generated by the photovoltaic panels is then stored in accumulators for the time when we need it for hydrogen production